Crapemyrtle Aphid, Sarucallis kahawaluokalani (Kirkaldy) (Insecta: Hemiptera: Aphididae) - John Herbert; Russ F. Mizell, III (EDIS)
EENY-365, a 4-page illustrated fact sheet by John Herbert and Russ F. Mizell, III, describes synonymy, distribution, description, biology, damage, management and ecological interactions of this pest of crapemyrtles. Includes selected references. This publication was originally published on the Featured Creatures Web site by the UF Department of Entomology and Nematology, February 2006.